2014
DOI: 10.1638/2013-0155r1.1
|View full text |Cite
|
Sign up to set email alerts
|

SEVERE WHIPWORM (TRICHURISSPP.) INFECTION IN THE DROMEDARY (CAMELUS DROMEDARIUS)

Abstract: One adult (13-yr-old) and two young (3-4-yr-old) male dromedary camels (Camelus dromedarius) from the Seoul Zoo displayed anorexia and chronic diarrhea for 2 wk. Direct fecal smear examination revealed Trichuris spp. infection. After confirmation of the infection, fenbendazole was orally administered as a suspension; this was repeated two times at 3-wk intervals. A high initial dose (20 mg/kg) was followed by administration at the recommended dose (10 mg/kg). Starting on the day following the first treatment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
1
5
0
1
Order By: Relevance
“…are significant parasites of camelids, and are resistant to treatment with the usual doses of anthelmintics which are effective for other GI nematodes. Fatal Trichurosis has been reported by Eo et al 2014 in Seoul Zoo with adult worms found attached to the wall of the large intestine and diarrhea present which is in conformation with our findings in this case. Adult parasites are found in the caecum and large intestine.…”
Section: Discussionsupporting
confidence: 91%
“…are significant parasites of camelids, and are resistant to treatment with the usual doses of anthelmintics which are effective for other GI nematodes. Fatal Trichurosis has been reported by Eo et al 2014 in Seoul Zoo with adult worms found attached to the wall of the large intestine and diarrhea present which is in conformation with our findings in this case. Adult parasites are found in the caecum and large intestine.…”
Section: Discussionsupporting
confidence: 91%
“…This animal expired and death was attributed to whipworm infestation (34). Two younger dromedaries 3-4 years of age at the Seoul Zoo developed anorexia and chronic diarrhea in association with whipworms (34). In this study, one case which was dead on arrival was identified as having whipworms with small intestinal and colonic enteritis.…”
Section: Discussionmentioning
confidence: 67%
“…In a case report from the Seoul Zoo, a 13-year-old dromedary developed mucohemorrhagic typhlitis and abomasal ulcers. This animal expired and death was attributed to whipworm infestation (34). Two younger dromedaries 3-4 years of age at the Seoul Zoo developed anorexia and chronic diarrhea in association with whipworms (34).…”
Section: Discussionmentioning
confidence: 99%
“…Вивчення гельмінтологічної ситуації зоопарків є актуальним з огляду на можливість дослідження екзотичних тварин, що перебувають на обмеженій території, та отримання колекційних екземплярів гельмінтів, не притаманних фауністичному складу свійських тварин (Kharchenko and Marunchin, 1992;Eo et al, 2014;Kyung-Yeon et al, 2014;Gressler et al, 2016;Seguel and Gottdenker, 2017).…”
Section: вступunclassified